GERIATRIC HEALTH SCREENING: AN INTERPROFESSIONAL EDUCATION OPPORTUNITY - Hudgins, G.A. (Innov Aging, 2017)
The Institute of Medicine, among other organizations, has established interprofessional education (IPE) as a goal for all health professions. Most academic accrediting agencies are now requiring activity in this area. Programs located in largely rural areas without an academic medical center may have more difficulty in achieving IPE for their students. The Montana Geriatric Workforce Enhancement Program at the University of Montana provides interdisciplinary student training through geriatric health screening. Pharmacy, nursing, medicine, physical therapy, social work, and speech pathology students from four Montana academic institutions participate. In a typical year, approximately 65 pharmacy students, 40 physical therapy students, 20 nursing students, 30 social work students, and varying numbers of students from other disciplines are involved in over 50 screening events held throughout the state. Under faculty supervision, teams of students provide screenings for older individuals in rural communities, including counseling on the results and follow up of abnormal values. Screenings for lipids, hemoglobin A1c, bone density, blood pressure, hepatitis C, balance testing and fall risk assessment, caregiver stress, cognition and depression are provided. Barriers to participation include varying formats and schedules for clinical training, requirements for appropriate supervision of students and identification of community referral resources. Approaches utilized by pharmacy, two different nursing programs, physical therapy, social work, speech pathology, and medicine will be described and compared. Evaluation results from surveys of faculty and students will be included.